2018
DOI: 10.1002/esp.4399
|View full text |Cite
|
Sign up to set email alerts
|

Removal of water‐surface reflection effects with a temporal minimum filter for UAV‐based shallow‐water photogrammetry

Abstract: The recent development of structure‐from‐motion (SfM) and multi‐view stereo (MVS) photogrammetry techniques has enabled semi‐automatic high‐resolution bathymetry using aerial images taken by consumer‐grade digital cameras mounted on unmanned aerial vehicles (UAVs). However, the applicability of these techniques is sometimes limited by sun and sky reflections at the water surface, which render the point‐cloud density and accuracy insufficient. In this research, we present a new imaging technique to suppress the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…They demonstrated that it is possible to quantify submerged geomorphic changes with levels of accuracy of less than 4 cm similar to that from exposed areas without the need of calibration data and that, using nadir imagery, the results obtained after different refraction corrections are practically the same. Partama et al [54] presented a novel technique based on co-registered image sequences or video frames to reduce the effects of water-surface reflection on UASbased photogrammetry. This promising method, applied in a river reach 0-1.5 m deep, achieved accuracies of 5-15 cm, clarified the reflected signal from the bottom bed and enabled to reduce moving light patterns.…”
Section: Bathymetry and Submerged Topographymentioning
confidence: 99%
“…They demonstrated that it is possible to quantify submerged geomorphic changes with levels of accuracy of less than 4 cm similar to that from exposed areas without the need of calibration data and that, using nadir imagery, the results obtained after different refraction corrections are practically the same. Partama et al [54] presented a novel technique based on co-registered image sequences or video frames to reduce the effects of water-surface reflection on UASbased photogrammetry. This promising method, applied in a river reach 0-1.5 m deep, achieved accuracies of 5-15 cm, clarified the reflected signal from the bottom bed and enabled to reduce moving light patterns.…”
Section: Bathymetry and Submerged Topographymentioning
confidence: 99%
“…This approach could enable depth retrieval from high spatial resolution, glint-contaminated image sequences that would be of no use if analyzed as individual frames. If the glint is extreme, using a temporal minimum filter, as suggested by Partama et al (2018), might be more effective than an averaged image. Other approaches to mitigating sun glint so as to achieve illumination invariance could be explored in future research and include contrast limited adaptive histogram equalization (Dal Sasso et al, 2020) and homomorphic filtering (Nnolim & Lee, 2008).…”
Section: Advantages and Extensions Of Ibarimentioning
confidence: 99%
“…For mapping an underwater area, authors in [26] used a "floating pyramid" for lifting two cameras. The base of the pyramid was made of Plexiglas for avoiding wave effects and sun glint, which according to [27], sometimes limits the performance of two-media approaches. A contemporary, but similar approach is adopted by [18] for mapping the bottom of a river.…”
Section: Analytical and Image-based Refraction Correctionmentioning
confidence: 99%